Planning, Monitoring, and Evaluation : Methods and Tools for Poverty and Inequality Reduction Programs - Busjeet, Gita (World Bank, Washington, DC, 2013)
As the author enter the second decade of the twenty-first century, governments, international organizations, nongovernmental organizations (NGOs), philanthropic organizations, and civil society groups worldwide are actively focusing on evidence-based policy and increased accountability to stakeholders (results agenda).The widespread implementation of the Results Agenda has generated a plethora of books, guides, academic papers, trainings, and case studies, which has enabled an ongoing maturation process in the field. Consequently, specialists are now better equipped to understand what works under which circumstances. Broadly speaking there are two interrelated questions which must be answered when assessing the sustainability of a government results agenda. First, is the institutional design and practice of government conducive to evidence-based policy making? Second, are the overarching monitoring and evaluation (M&E) methods and specific tools used appropriate for garnering the evidence demanded by government? These series of notes aim to make a small contribution to the latter question by summarizing and highlighting a selection of PM&E methods and the tools that governments and international organizations around the world have developed to put these into practice in their own contexts. The central goal of this initiative is to prompt a process of learning, reflection and action by providing practical information to those whose leadership role requires them to understand PM&E methods and their potential for enhancing evidence-based policy making.